2007
DOI: 10.1158/0008-5472.can-06-4338
|View full text |Cite
|
Sign up to set email alerts
|

PTP1B Contributes to the Oncogenic Properties of Colon Cancer Cells through Src Activation

Abstract: Src-specific activity has been reported to be elevated in a high percentage of colon cancer cell lines and tumors, but the underlying mechanisms are largely unknown. In this study, we report that, in the seven cancer cell lines tested, Src-specific activity was elevated (5.2-to 18.7-fold) relative to normal colon cells (FHC). This activation of Src correlated with reduced phosphorylation at Y530 of Src, whereas there was no significant change in the level of phosphorylation at Y419. The membrane tyrosine phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
122
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(129 citation statements)
references
References 45 publications
(67 reference statements)
6
122
1
Order By: Relevance
“…We found that the specific activity of Src kinase (activity per molecule) was greatly increased in all seven of the colon cancer cell lines tested, including SW48, DLD-1, HCT 116, HT-29, Caco-2, COLO 201 and LS 174T, as compared to the normal colon cell lines FHC and CCD18Co, ranging from 5.2-to 18.7-fold (Zhu et al, 2007), indicating that Src is activated in these cancer cell lines.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…We found that the specific activity of Src kinase (activity per molecule) was greatly increased in all seven of the colon cancer cell lines tested, including SW48, DLD-1, HCT 116, HT-29, Caco-2, COLO 201 and LS 174T, as compared to the normal colon cell lines FHC and CCD18Co, ranging from 5.2-to 18.7-fold (Zhu et al, 2007), indicating that Src is activated in these cancer cell lines.…”
Section: Resultsmentioning
confidence: 89%
“…In breast cancer, colon cancer and pancreatic cancer, Src kinase activity has been found to be elevated (reviewed in Irby and Yeatman, 2000). Downregulating Src activity with antisense RNA in the colon cancer cell line HT-29 (Staley et al, 1997) or with siRNA in the colon cancer cell line SW48 (Zhu et al, 2007) reduces colony formation numbers in soft agar, demonstrating that elevated Src activity plays an important role in colon cancer tumorigenicity.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, several candidates have been suggested to disrupt the SH2-pTyr529 intramolecular interaction. These include growth factor receptors, through their association with SFK-SH2 (Mao et al, 1997), and tyrosine phosphatases that dephosphorylate pTyr529 (Liang et al, 2007;Zhu et al, 2007;Zheng et al, 2008). Although probably activated in a subset of tumours, they may not account for the kinase deregulation observed in CRC.…”
Section: Introductionmentioning
confidence: 99%
“…PTP1B protein levels have been observed to be upregulated in various human cancers such as breast and ovarian cancers (13,14). Ablation or inhibition of PTP1B activity can abrogate the malignant properties of prostate cancer cells, whereas PTP1B overexpression promoted the growth of gastric and colon tumor cells (15)(16)(17). In our studies, we identified PTP1B as a downstream effector of the CRT pathway.…”
Section: Discussionmentioning
confidence: 55%